The national survey of academic researchers: New facts and data - Kyle Myers; Wei Yang Tham; Jerry Thursby; Marie Thursby; Nina Cohodes; Karim Lakhani; Rachel Mural; Yilun Xu (PLoS ONE, 2026)
We introduce a new survey of professors at roughly 150 of the most research-intensive institutions of higher education in the US. We document seven new features of how research-active professors are compensated, how they spend their time, and how they perceive their research pursuits, which we organize under three themes. Earnings and inequality: (1) there is more inequality in earnings within fields than there is across fields; (2) institutions, ranks, tasks, and sources of earnings can account for roughly half of the total variation in earnings; (3) there is significant variation across fields in the correlations between earnings and different kinds of research output, but these account for a small amount of earnings variation. Research productivity and inputs : (4) measuring professors’ productivity in terms of output-per-year versus output-per-research-hour can yield substantial differences; (5) professors’ beliefs about the riskiness of their research are best predicted by their fundraising intensity, their risk aversion in their personal lives, and the degree to which their research involves generating new hypotheses. Research output choices: (6) older and younger professors have very different research outputs and time allocations, but their intended audiences are quite similar; (7) personal risk-taking is highly predictive of professors’ orientation towards applied, commercially relevant research. An anonymized version of the data is publicly available at: https://tny.sh/nsar .